Effect of Sterculia quadrifide Extract R.Br. Against Free Radical In Liver Organs Oreochromis niloticus Due to Heavy Metal Pollution - Janes Bastian Selly; Abdurrouf Abdurrouf; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2015)
Sterculia quadrifida R.Br. is known with the name of Faloak. It is a plant whose bark has been containing several natural antioxidant compounds. Research shows that antioxidant compounds of Faloak extract can reduce free radicals content in liver organ of nila fish (Oreochromis niloticus) that is contamined by metals such as Pb, Cd and Hg. The concentration of metals is directly proportional with free radicals content of the organ, but free radicals content is inversely proportional with the concentration of faloak extract. Result of research indicates that faloak concentration of 16,00mg/mL is the most effective concentration in reducing free radicals content in liver organ of nila fish. Type and content of free radicals in the organ are identified with Electron Spin Resonance (ESR) test.